[OP.3A.03] MINERAL, BONE METABOLISM MARKERS AND ARTERIAL STIFFNESS IN DIALYSIS POPULATION. (September 2017) - Desbiens, L.; Munger, M.; Ung, R.-V.; Sidibé, A.; Wang, Y.-P.; Fortier, C.; Agharazii, M.; Marquis, K.; Mac-way, F.
Abstract : Objective: Mineral and bone disorders in Chronic Kidney Disease (CKD) are associated with increased arterial stiffness, cardiovascular events, and mortality. This study aims to determine the association between new bone markers (Sclerostin, DKK1, α-Klotho, FGF23) and parameters of arterial stiffness (central and peripheral) and mortality in a dialysis population. Design and method: Cross-sectional and retrospective study of hemodialysis patients that have been previously recruited for the study of arterial stiffness at CHU de Québec, Canada. Demographic, clinical, pharmacological, mineral, biochemical parameters and mortality were collected. Bone markers levels of Sclerostin, DKK1, α-Klotho, FGF23, P1NP and TRAP5b were obtained by ELISA from pre-dialytic plasma. Carotid-femoral (CF) and carotid-radial (CR) pulse-wave velocity (PWV) and femoral/radial PWV ratio were measured in every patient as previously performed. Linear and Cox regression analysis were used to assess factors associated with arterial stiffness and mortality. Results: We included 130 hemodialysis patients with a median follow-up of 1290 (864) days. Population characteristics are presented in table 1. The population is composed of 47% male with a mean age of 72 (±14) years and a mean dialysis vintage of 545 (1171) days. 56% had coronary artery disease, 51% had diabetes and 89% suffered from hypertension. At the end of follow-up, 97 (75%) patients had died. Median CF-PWV was 13, 5 (5, 1) m/s, CR-PWV was 8, 4 (2, 0) m/s and PWV-ratio was 1, 7 (0, 7). In univariate analysis, as displayed in table 2, only FGF23 blood level was inversely associated with CF-PWV while α-Klotho and Sclerostin were positively associated with CR-PWV. FGF23, α-Klotho and Sclerostin levels were inversely associated with the PWV ratio. In multivariate models adjusting for demographic, biochemical and mineral parameters, α-Klotho was positively associated with CR-PWV and inversely associated with the PWV ratio. Finally, only FGF23 levels were associated with an increased mortality in both univariate and multivariate models. Figure. No caption available. Conclusions: In a dialysis population, plasma levels of α-Klotho and Sclerostin are associated with peripheral arterial stiffness and femoral/radial stiffness ratio. High levels of FGF23 are associated with increased mortality. These results suggest a central role of mineral parameters in arterial stiffness in CKD.